Navigating the Digital Landscape: Unveiling Language Dynamics and Digital Identity among Indonesia’s Contemporary Generation - Wagiati, Wagiati; Darmayanti, Nani; Adji, Muhammad (Fakultas Seni Rupa dan Desain ITB, 2024)
This research article investigates the impact of the Internet on language development and digital linguistics in Indonesia. It explores the search frequency and familiarity trends of Indonesian words and phrases, examining their connection to social change and identity. The study utilizes the Google Trend platform to collect data from 2018 to 2023, capturing the prevalence of the Indonesian language in Google searches. The research incorporates a comparative analysis of online data from social media, incorporating ethnographic interviews with 30 participants, and conducting a comprehensive lexicon survey. 77 Indonesian words and phrases are collected and analyzed, providing insights into familiarity patterns. Additionally, interviews and surveys are conducted with Indonesian university students to understand their attitudes towards language, its role in shaping identities, internet usage, and societal norms. The analysis focuses on 40 selected words, investigating their correlation with language patterns, identity formation, emotions, and societal conventions. The findings reveal how neologisms within Indonesia’s digital linguistic landscape reflect societal shifts, including contemporary events, social media trends, and societal pressures. The proliferation of trending words aligned with themes of identity, societal norms, and emotional well-being highlights the influence of social media and the Internet on language dissemination. These changes are deeply embedded in Indonesia’s digital linguistic milieu and are further elucidated through interviews, offering insights into internet users’ linguistic practices. The study emphasizes the importance of tracking language and societal trends for self-expression and integration into diverse communities. It also highlights the reciprocal relationship between self-identity and communal influence on language development. This research contributes to understanding language dynamics and digital identity in the Indonesian context, revealing the complex interplay between language, society, and individual perspectives.